STATISTICALLY SIGNIFICANT DIFFERENCES OF CHILDREN’S EMOTIONALLY DESTRUCTIVE BEHAVIOR DEPENDING ON THE LEVEL OF ITS MANIFESTATION - Yacishina, Anastacia (PSYCHOLOGICAL JOURNAL, 2019)
The problem of emotionally destructive behavior is quite topical both in theoretical and practical aspects. The urgency of this problem is conditioned primarily by the fact that children’s destructiveness is manifested quite often and this complicates the learning and educational process. The author analyzes several approaches to understanding the psychological content of emotionally destructive behavior: the first approach is based on purely linguistic approaches to understanding this category; the second approach considers emotionally destructive behavior based on the direction of the speciality, activity or field of knowledge; the third approach, when defining emotionally destructive behavior, traces other, similar in their names interpretations. It is revealed that emotionally destructive behavior is the process of inadequate actions aimed at complicating the interaction of the individual with the social environment. To achieve the goal and accomplish the objectives of the research, the following methods were used: theoretical (analysis of domestic and foreign scientific sources, generalization of concepts and approaches underlying the destructive behavior and its features). To solve the tasks, a theoretical analysis of scientific papers was carried out. The purpose of the article is to study the emotionally destructive behavior in children of primary school age, depending on the frequency of its manifestation. To solve the tasks, a specially designed author’s questionnaire was used. According to the statistical analysis of differences in the severity of the studied parameters in groups of children with different frequency of manifesting emotionally destructive behavior signs, children with a high frequency of manifestation differ significantly from the children with optimal emotionally destructive behavior, they demonstrate much more inconsistent, unpredictable behavior, are stubborn, easily agitated, conflict-oriented, quick-tempered, cruel, rapid, ill willed, have more biased attitude towards others, often manifest aggression, inappropriate actions and destruction of things. The data obtained can be employed for methodical guidelines to be used by teachers, psychologists and parents.